2021
DOI: 10.3389/fpsyt.2021.745215
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Staff Attitudes to Coercion in Poland

Abstract: Introduction: Coercion can be defined as the use of force to limit a person's choices. In Poland, coercive measures may tend to be overused. However, there is limited information regarding the attitudes of nurses toward coercion in psychiatric settings and the factors influencing any decisions to use coercion.Aims: To validate the Staff Attitudes to Coercion Scale (SACS) for a group of psychiatric nurses and psychiatrists, to compare the said with the original Norwegian SACS version, and to compare nurses' att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…As for item 4, “Use of coercion is a declaration of failure on the part of the mental health services,” it did not load on any factors in our EFA. It seemed to suggest a common problem observed in previous studies that developed the Polish version of SACS, which reported almost the same factor structure with the original version, except for item 4 ( 18 , 19 ). The term “a declaration of failure” might be confusing or evoke different images among respondents.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As for item 4, “Use of coercion is a declaration of failure on the part of the mental health services,” it did not load on any factors in our EFA. It seemed to suggest a common problem observed in previous studies that developed the Polish version of SACS, which reported almost the same factor structure with the original version, except for item 4 ( 18 , 19 ). The term “a declaration of failure” might be confusing or evoke different images among respondents.…”
Section: Discussionmentioning
confidence: 68%
“…It was thought that a hope of decreasing the use of coercion was derived from the undesirableness of its use. Concerning the results of factor analyses conducted in the other language versions of the SACS, the original three-factor structure was almost replicated in the Polish version ( 18 , 19 ), but not in the German version, which offered a one-factor structure ranging from rejecting to approving the use of coercion ( 20 ). Studies on the factor structure of the SACS is limited ( 17 ) and further studies are needed.…”
Section: Discussionmentioning
confidence: 94%
“…Two studies analyzed the single items, and not the three subscales (28,47). Three studies confirmed the original three-factor model (25,27,28), and one study found that a one-factor model was better suited (26).…”
Section: How Has the Sacs Questionnaire Been Used?mentioning
confidence: 83%
“…One study used a yes/no response instead of the original five-point Likert scale (30), and one study had used a four-point scale (36). Five of the studies had only translation and validation as its purpose (24)(25)(26)(27)(28). Two studies analyzed the single items, and not the three subscales (28,47).…”
Section: How Has the Sacs Questionnaire Been Used?mentioning
confidence: 99%
See 1 more Smart Citation